Bermudian English a sociohistorical and linguistic profile - Eberle, Nicole (Varieties of English around the world,, 2021)
"Bermudian English. A sociohistorical and linguistic profile focuses on a hitherto severely under-researched variety of English. The book traces the origins and development of Bermudian English, so as to situate the variety within the canon of other lesser-known varieties of English, and provides a first in-depth description of its variable morphosyntactic structure. Relying on sociolinguistic interview data and combining qualitative, typological and quantitative, variationist analyses of selected morphosyntactic features, it sheds light on structural affiliations of Bermudian English and argues for a two-way transfer pattern where Bermudian English plays an important role in the development of a number of other English(-based) varieties in the wider geographical region. Complementing existing studies which document such varieties, this book contributes to the body of research that describes the diversity of English(-based) varieties around the globe, filling a notable gap"--